Implementing person centred dementia care: a musical intervention. Issue 2 (8th June 2015) - Argyle, Elaine; Kelly, Tony
Abstract : Purpose: – Recent years have seen the advocacy of person-centred approaches to dementia care. An important component of this approach has been the use of arts in the promotion of health and well-being. However, relatively little attention has been given to the barriers and facilitators experienced in trying to implement these types of interventions in a dementia care setting. It is therefore, the purpose of this paper is to help to redress this neglect by examining the process of implementing a personalised musical intervention for the clients of a specialist dementia home care service. Design/methodology/approach: – Drawing on interviews with five project stakeholders, the paper examines, not only the potential benefits to be gained from the musical intervention but also identifies the barriers experienced in its implementation and ways in which they could be overcome. Findings: – It was found that although the musical intervention had a potentially positive impact, there were multi-levelled barriers to its implementation including issues of training, leadership as well as contextual issues such as commissioning and resourcing more generally. Originality/value: – The key role played by these issues in the process of implementation suggests that practice should transcend its focus on individual wellbeing and address the wider factors that can facilitate or prevent its fulfilment. While the multi-levelled nature of the obstacles identified suggest that the implementation of innovative interventions within health and social care settings should adopt a similarly eclectic approach.